UNSUR PEMBELAJARAN EDUTAINMENT DALAM QUANTUM LEARNING - Purwanto, Setyoadi (Universitas Islam Sultan Agung, 2019)
Early childhood learning uses the principle of playing while learning so that it must be arranged so that it is fun, uplifting, and democratic. Quantum Learning is a learning method that is loaded with edutainment concepts. Based on the studies conducted, the following conclusions are obtained: (1) Quantum learning and edutainment both emphasize the urgency of a pleasant and easy atmosphere; (2) Equally starting from the world of non-education; (3) Both give primary attention to an exciting learning process, which involves physical-sensory, emotional, and suggestive beliefs; (4) Quantum learning and edutaintment are able to foster student confidence; (5) Quantum learning builds student learning skills through a variety of cutting-edge discoveries, and edutainment continually seeks to facilitate optimal learning processes; (6) Quantum learning and edutaintment simultaneously build effective communication to students.Â Keywords: learning, quantum learning, edutaintmen